(untitled) ("Temas Sociais" Journal, 2023)
The main objective of this investigation is to study the factories that could jeopardize the sustainability of IPSS, in the area of disability and in particular, cerebral Palsy. For that, the quantitative method was used through a questionnaire by survey and by the analysis of the balance she ets and income statements .The interpretation of these results, it is intended to determine which are the factors of sustainability, which are the risk zones they face namely indebtedness, to identify the areas likely to create value, formulate possible recommendations, and prioritize initiatives for the implementation of a transformation program.This study also sought to innovate creating a guiding and limiting framework for zones at risk of loss of sustainability, a map that could be used by IPSS technicians, to detect the appearance of such symptoms.